Literature Study on the Use of Big Data and Artificial Intelligence in Policy Making in Indonesia - Supriyanto, Eko Eddya; Warsono, Hardi; Herawati, Augusin Rina (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2021)
The use of big data and artificial intelligence in decision making in Indonesia is still rarely implemented. But in the business world, big data and artificial intelligence are very commonplace to boost targets. This study discusses the use of big data and artificial intelligence in policy Making in Indonesia. The method used in this paper is qualitative research with a literature study approach. The result of this research is that the dynamics in the implementation of public services require appropriate and fast decision making, considering that this is a community demand. Therefore, public leaders need to disrupt themselves in public services so that these services can be served quickly. In conclusion, big data and artificial intelligence can help public leaders make decisions to deliver the best policies.